An In Vitro study of Fracture Resistance of Weakened Tooth Roots Reinforced with Two Types of Adhesive Restorative Materials (Bangladesh Journal of Medical Science, 2013)
Introduction: Composite resin (CR) is among the commonly used material for intraradicular reinforcement of weakened tooth roots. Purpose: This study was to compare the fracture resistance of experimentally weakened tooth roots reinforced using auto-polymerized composite resin and light-polymerized composite resin. Materials and Methods: Fifty-six extracted human maxillary incisors were divided into 2 groups (n = 28) and the root canals were over prepared to weaken it. The samples in Group Awere restored using lightcured CR Z100 and light-transmitting polymerizing post (Luminex), whereas Group B using auto-cured CR Alpha-dent. Both groups were placed with metal parapost cemented with a resin luting cement (Nexus 2). Specimens were subjected to compressive load (N) using Instron machine until fracture. Data were submitted to independent t test analysis of variance (p < 0.05). Results: There was no significant difference (p = 0.233) in fracture resistance between the teeth reinforced with light-polymerizing and auto-polymerizing CR are 549.3 (± 95.44) and 490.7 (± 110.37) respectively. Conclusion: The use of less technique sensitive autopolymerizing CR give equivalent benefit effect on reinforcing weakened roots, as the more commonly lightpolymerized composite resin. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13353 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.63-67